CHALLENGES AND SELF-EFFICACY OF PRIMARY SCHOOL TEACHERS IN SUPPORTING LEARNING OF STUDENTS WITH AUTISM SPECTRUM DISORDERS IN INCLUSIVE CLASSROOM IN LOMBOK TIMUR - Saputra, Ahmad Yudi; Aziz, Nurbieta Binti Abd; Al Fadhil, M. (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2025)
There is general support among teachers for the inclusion of students with special educational needs, but many lack the confidence and knowledge to support students with autism spectrum disorder (ASD). This can be harmful and detrimental to their education. A qualitative study of teachers' perceptions of inclusion found that teachers' views influenced the way in which inclusive practices were implemented. This research used semi-structured interviews and interview transcripts to facilitate data analysis with eight teachers in mainstream and special schools. Questions explore school-based provision for students with ASD, including strategies related to classroom learning. Thematic analysis identifies themes that describe teachers' challenges and self-efficacy in supporting students with ASD, the supports they use to facilitate success, and the influence of factors such as trust, empathy, praise, caring, guidance and pedagogical support. The results showed that most teachers felt anxious and lacked confidence about the early prospects of teaching students with ASD. The results showed that most teachers felt anxious and lacked confidence about the early prospects of teaching pupils with ASD. Most teachers who responded to the questionnaire also described feelings of insecurity about managing the behaviour of students with ASD. These findings were analysed in relation to teachers' perceptions of learning problems such as lack of access to resources, learning support and training in ASD-specific approaches.